Increasing taxon sampling suggests a complete taxonomic rearrangement in Echinantherini (Serpentes: Dipsadidae) - Abegg, Arthur D.; Santos, Alfredo P.; Costa, Henrique C.; Battilana, Jaqueline; Graboski, Roberta; Vianna, Fernanda S. L.; Azevedo, Weverton S.; Fagundes, Nelson J. R.; Castille, Clément M.; Prado, Pedro C.; Bonatto, Sandro L.; Zaher, Hussam; et al. (Frontiers in Ecology and Evolution, 2022)
Although the recent advances on the relationship of its major groups, the systematics of the rich fauna of neotropical snakes is far from been a consensus. In this sense, derived groups presenting continental distributions have represented a main challenge. The taxonomy of the snake tribe Echinantherini is one of the most contentious among the diverse family known as Dipsadidae. The tribe is poorly sampled in phylogenetic studies, resulting in conflicting hypotheses of relationships among its taxa. Moreover, several rare and micro endemic species of Echinantherini have never been evaluated within a comprehensive phylogenetic framework. Here, we assess for the first time the phylogenetic position of the rare Echinanthera amoena within Echinantherini. We based our analyses on a comprehensive multilocus dataset including 14 of the 16 species described for the tribe. Our results support the monophyly of Echinantherini and strongly indicate E. amoena as a unique lineage, phylogenetically positioned apart from all other congeners. From the three current genera (Echinanthera, Taeniophallus and Sordellina) our results indicate that Echinanthera and Taeniophallus are paraphyletic, since the T. affinis species group is positioned as sister to Echinanthera (except E. amoena) clustering apart from the clade formed by the T. brevirostris and T. occipitalis groups. We describe new genera for the T. affinis and T. occipitalis species groups and an additional monospecific genus for E. amoena. Although we did not evaluate the phylogenetic position of T. nebularis, we described a new genus and removed it from Echinantherini since its morphology strikingly departs from all species now included in the tribe. Finally, we redefine the genera Echinanthera and Taeniophallus and we provide comments about further directions to study the biogeography and the evolution of morphological traits in Echinantherini.